PENGARUH BUDAYA PERUSAHAAN TERHADAP PRESTASI KERJA KARYAWAN PT PEMBANGKITAN JAWA-BALI SURABAYA UNIT PELAYANAN PEMELIHARAAN - Riyan Sisiawan Putra (Jurnal Manajemen dan Wirausaha, 2013)
A strong application of corporate culture drives a company in improving its performance and achieving its targets. With the result that the corporate culture has a role in increasing the welfare of it’s employees. The purpose of this study was to determine the relationship between the variables of corporate culture, employee motivation and employee performance. Path Analysis technique was utilised to analyse the obtained data. The results showed significant influences between work motivation on corporate culture, corporate culture on employee performance and work motivation on employee performance of PT Power Java-Bali, maintenance services unit of Surabaya.